2016
DOI: 10.1038/srep20931
|View full text |Cite
|
Sign up to set email alerts
|

LPS causes pericyte loss and microvascular dysfunction via disruption of Sirt3/angiopoietins/Tie-2 and HIF-2α/Notch3 pathways

Abstract: Recent studies reveal a crucial role of pericyte loss in sepsis-associated microvascular dysfunction. Sirtuin 3 (SIRT3) mediates histone protein post-translational modification related to aging and ischemic disease. This study investigated the involvement of SIRT3 in LPS-induced pericyte loss and microvascular dysfunction. Mice were exposed to LPS, expression of Sirt3, HIF-2α, Notch3 and angiopoietins/Tie-2, pericyte/endothelial (EC) coverage and vascular permeability were assessed. Mice treated with LPS signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 49 publications
4
78
0
Order By: Relevance
“…To address that question, SIRT3 −/− mice with additional backcrosses should be tested. SIRT3 +/+ mice had a minor yet significant survival advantage (10% vs 0% survival in SIRT3 +/+ vs SIRT3 −/− mice) in a highly stringent model of endotoxemia 38 , suggesting that SIRT3 may provide benefits in sterile, deep inflammatory, processes. Unfortunately, the cytokine response was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…To address that question, SIRT3 −/− mice with additional backcrosses should be tested. SIRT3 +/+ mice had a minor yet significant survival advantage (10% vs 0% survival in SIRT3 +/+ vs SIRT3 −/− mice) in a highly stringent model of endotoxemia 38 , suggesting that SIRT3 may provide benefits in sterile, deep inflammatory, processes. Unfortunately, the cytokine response was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ang-1 is critical for the vascular integrity, stability, and EC survival, as well as pericyte recruitment. Our recent study demonstrated a critical role of SIRT3 in LPS-mediated pericyte loss, vascular leakage and cardiac dysfunction [39]. Microvascular dysfunction could be related to the changes in both function and morphology of the microcirculation [5;40].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of pericytes is an early hallmark of diabetic retinopathy and leads to microaneurysm due to reduced vessel integrity . Inducing inflammation with lipopolysaccharide treatment leads to pericyte loss and microvascular dysfunction in a mouse model of sepsis . Furthermore, loss of pericytes accelerates Aβ accumulation, the appearance of Tau pathology and neuronal degeneration in mice overexpressing Aβ‐precursor protein .…”
Section: Therapeutic Potential Of Svfmentioning
confidence: 99%